Communicating BRCA research results to patients enrolled in international clinical trials: lessons learnt from the AGO-OVAR 16 study. Issue 1 (December 2016) - Pulford, David; Harter, Philipp; Floquet, Anne; Barrett, Catherine; Suh, Dong; Friedlander, Michael; Arranz, José; Hasegawa, Kosei; Tada, Hiroomi; Vuylsteke, Peter; Mirza, Mansoor; Donadello, Nicoletta; et al.
Abstract Background The focus on translational research in clinical trials has the potential to generate clinically relevant genetic data that could have importance to patients. This raises challenging questions about communicating relevant genetic research results to individual patients. Methods An exploratory pharmacogenetic analysis was conducted in the international ovarian cancer phase III trial, AGO-OVAR 16, which found that patients with clinically important germ-lineBRCA1/2 mutations had improved progression-free survival prognosis. Mechanisms to communicateBRCA results were evaluated, because these findings may be beneficial to patients and their families. Results Communicating individualBRCA results was not anticipated during clinical trial design. Consequently, options were not available for patients to indicate their preference for receiving their individual results when they signed pharmacogenetic informed consent. Differences in local requirements, clinical practice, and opinion regarding the ethical aspects of how to convey genetic results to patients are all potential barriers to returning individualBRCA results to patients. Communicating the aggregateBRCA result from this study provided clinical investigators with a mechanism to disseminate the overall study finding to patients while taking individual circumstances, local guidelines and clinical practice into account. Conclusion This study illustrates the importance of increasing the clarity and scope of informed consent and the need for patient engagement to ensure clinical trial participants can indicate their preference regarding receipt of potentially important individual pharmacogenetic results. Trial registration This study was registered in the NCT Clinical Trial Registry underNCT00866697 on March 19, 2009, following approval from participating ethics committees (Additional file 1).